Pengembangan UMKM dengan Menerapkan Penjualan Melalui E-Commerce dan Pelatihan Manajemen Waktu di Masa Pandemic Covid-19 - Silvia Sari; Rini Septiowati; Purwatiningsih Purwatiningsih; Ruruh Dyatmiko; Widayat Widayat (Abdimisi, 2020)
Community Service entitled UMKM Development by implementing sales through e-commerce and time management training during the Covid-19 pandemic aims to provide knowledge about sales through e-commerce and time management training, invite and instil awareness to UMKM actors that it is very It is important to develop marketing through e-commerce and time management to survive the Covid pandemic. The target of this service is all UMKM members who are in Bumi Mas Ciseeng Housing, Kuripan Village, Ciseeng - Bogor. The results of this PKM are proven that UMKM players can master the way of selling through e-commerce and time management training so that they can survive during the Covid-19 pandemic.